Educar com sabor & saber: relatos e vivências interdisciplinares nas aulas de nutrição e gastronomia em instituições abertas para a terceira idade - Tomazoni, Ana Maria Ruiz (2009)
During the 20th Century, worldwide, the old-aged population increased considerably and, therefore, laws, documents and new ways of dealing with oldness were created. Along with the human progress, raised the necessity of thinking positively about the oldness and the quality of life of this population. Oldness, then, started being seen and lived as a period in which it is still possible to be productive, to maintain the self-esteem and the success. This essay was conducted taking into consideration the gerontology scope and its main theme involves the education addressed to food, healthy and gastronomy. The main objective was to investigate and describe the probable changes brought to the old-aged students lives by the new nutrition techniques, gastronomy guidance; etiquette tips, etc. The idea was to analyze old-aged people within an interdisciplinary vision and, for that, during theory classes, guides, books, texts and activities developed by several institutions were used. During practical classes in free opened to oldness institutions, five-senses workshops were developed, using etiquette practices, alive food, degustation, gastronomic excursions, between other experiences, in which the professor could interfere in the old-aged students day-by-day. It is important to point out that this is an interdisciplinary investigation based on questionnaires and memorials. Further to that, the results of these investigations were compared with other investigations conducted in Brazil and abroad aiming to validate and/or refute its results. Considering the answers of the questionnaires, it was possible to identify alterations in old-aged people nourishment, considering the consumption of healthier food, such as fruits, vegetables, water, more attention to ceremonials and formalities in general and themselves. Finally, we aimed to register a contribution to gerontology, considering old-aged people in a context of permanent education and contemplating them as active, respected and integrated human beings